Commissioner Diversity and Financial Restatement - Rustiarini, Ni Wayan; Kirani, Ni Putu Ika Candra; Asih, Ni Wayan Eka Purnami (E-Jurnal Akuntansi; Vol 33 No 5 (2023), 2023)
The phenomenon of financial restatement raises public questions regarding the effectiveness of corporate governance, particularly the role of commissioners as supervisory boards. One of the factors that influence the supervisory function is the diversity of commissioners. The research aims to analyze the role of the diversity of commissioners on financial restatements. Diversity is viewed from three aspects, namely independent commissioners, foreign commissioners, and female commissioners. The sample consists of 126 companies listed on the IDX. Data were analyzed using logistic regression. Statistical tests show that there are two variables that affect the financial restatement, namely foreign commissioners and female commissioners. However, the two variables have opposite directions. The existence of female commissioners empirically reduces financial restatements, while foreign commissioners increase the potential for financial restatements. Conversely, independent commissioners have no effect on the financial restatement. Keywords: Commissioner; Diversity; Female